Remembering the Personal Past: Beyond the Boundaries of Imagination - McCarroll, Christopher Jude (Frontiers in Psychology, 2020)
What is the relation between episodic memory and episodic (or experiential) imagination? According to the causal theory of memory, memory differs from imagination because remembering entails the existence of a continuous causal connection between one’s original experience of an event and one’s subsequent memory, a connection that is maintained by a memory trace. The simulation theory rejects this conception of memory, arguing against the necessity of a memory trace for successful remembering. I show that the simulation theory faces two serious problems, which are better explained by appealing to a causal connection maintained by a memory trace. Remembering the personal past is not the same as imagining.